The "boatman's knot": a new option for renal hilum ligation during laparoscopic nephrectomy - Bomfim,Alexandre C. (2005)
PURPOSE: The authors present and describe an original adaptation for the use of "boatman's knot" in renal vein ligation during laparoscopic nephrectomy. This procedure may replace the need for the endovascular stapler, which is considered the standard of care, but not available in several institutions in Brazil. The knot presented is also known as the " pig's knot" in several farms in Brazil. METHODS: Fourteen laparoscopic nephrectomies were performed by the same surgeon in a standard fashion in seven female pigs. Both the renal artery and vein were ligated using the "boatman's knot" as the only method for hemostasis with conventional intracorporeal technique. Two knots were applied in each artery and vein; one knot was tied proximally and the other distally. The vessels were then sectioned in between both knots. This technique is based on the intracorporeal confection of two loops by the right hand pair of dissectors with the help of the left hand. The arteries and the veins were then sectioned and the capability to accomplish full hemostasis was observed. RESULTS: All the laparoscopic nephrectomies were performed successfully. The "boatman's knot" was performed by the same surgeon with neither complications nor difficulties during the confection of the knot. In all cases hemostasis was fully achieved using only the "boatman's knot" as the hemostatic method. CONCLUSION: The "boatman's knot" is feasible and safe for hilum control during laparoscopic nephrectomy in pigs and total hemostasis can be achieved using it as the only method of hemostasis. However, the safety and the capacity of others to learn how to apply it should be tested before it may be advised to use it routinely.